Sex-based differences in metabolic protection by the ANP genetic variant rs5068 in the general population - Ichiki, Tomoko; Cannone, Valentina; Scott, Christopher G.; Iyer, Seethalakshmi R.; Sangaralingham, S. Jeson; Bailey, Kent R.; Goetze, Jens P.; Tsuji, Yoshihisa; Rodeheffer, Richard J.; Burnett, John C. (American journal of physiology. Heart and circulatory physiology, 2023)
Males are characterized by lower ANP and BNP with greater prevalence of cardiometabolic disease. The ANP genetic variant rs5068 was associated with less metabolic dysfunction in males, whereas no metabolic profile was related to the BNP genetic variant rs198389 in the general population. ANP may play a more biological role in metabolic homeostasis compared with BNP in the general population with greater physiological metabolic actions in males compared with females. Atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) are produced in the heart and secreted into the circulation. As hormones, both peptides activate the guanylyl cyclase receptor A (GC-A), playing a role in blood pressure (BP) regulation. A significant role for ANP and BNP includes favorable actions in metabolic homeostasis. Sex-based high prevalence of risk factors for cardiovascular disease in males compared with females is well established, but sex-based differences on cardiometabolic protection have not been investigated in relation to ANP ( NPPA) and BNP ( NPPB) gene variants. We included 1,146 subjects in the general population from Olmsted County, Minnesota. Subjects were genotyped for the ANP gene variant rs5068 and BNP gene variant rs198389. Cardiometabolic parameters and medical records were reviewed. In the presence of the minor allele of rs5068, diastolic BP, creatinine, body mass index (BMI), waist measurement, insulin, and prevalence of obesity and metabolic syndrome were lower, whereas HDL was higher in males with only trends observed in females. We observed no associations of the minor allele with echocardiographic parameters in either males or females. Regarding rs198389 genotype, the minor allele was not associated with any BP, metabolic, renal, or echocardiographic parameters in either sex. In the general community, the minor allele of the ANP gene variant rs5068 is associated with a favorable metabolic phenotype in males. No associations were observed with the BNP gene variant rs198389. These studies support a protective role of the ANP pathway on metabolic function and underscore the importance of sex in relationship to natriuretic peptide responses. NEW & NOTEWORTHY Males are characterized by lower ANP and BNP with greater prevalence of cardiometabolic disease. The ANP genetic variant rs5068 was associated with less metabolic dysfunction in males, whereas no metabolic profile was related to the BNP genetic variant rs198389 in the general population. ANP may play a more biological role in metabolic homeostasis compared with BNP in the general population with greater physiological metabolic actions in males compared with females.